2015
DOI: 10.1007/s11249-015-0559-5
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Performance and Lubrication Mechanism of Contact-Charged Electrostatic Spray Lubrication Technique

Abstract: To minimize friction at the chip-tool interface and the amount of lubricant usage, a new near-dry machining technique called ''contact-charged electrostatic spray lubrication (CCESL) technique'' was proposed. The chargeability, penetrability, and wettability of lubricant droplets under CCESL condition were analyzed. The atomization and tribological performance of the CCESL technique were compared with those of the existing minimal quantity lubrication (MQL) technique under different testing conditions. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Their results showed that CMR increased with the growth of voltage under all conditions [224,225]. Given that the tested liquids were nonpolar and better insulating specimens, the droplets were less chargeable at the lower voltages, as verified also in the experiments of Wang et al, who concluded that the higher the conductivity, the greater the chargeability of the liquid [233].…”
Section: Atomization Mechanism and Performance Assessmentmentioning
confidence: 67%
See 2 more Smart Citations
“…Their results showed that CMR increased with the growth of voltage under all conditions [224,225]. Given that the tested liquids were nonpolar and better insulating specimens, the droplets were less chargeable at the lower voltages, as verified also in the experiments of Wang et al, who concluded that the higher the conductivity, the greater the chargeability of the liquid [233].…”
Section: Atomization Mechanism and Performance Assessmentmentioning
confidence: 67%
“…the diameter of a sphere with the same volume and surface area ratio as the particles, which is used to estimate the average size of a given particle distribution [222,223]). The SMD of the droplets obtained at a charging voltage of −12 kV was 34.3% smaller than that obtained by MQL [224]. This result indicates that the atomization quality of the EMQL is higher than that of the conventional air-assisted MQL.…”
Section: Atomization Mechanism and Performance Assessmentmentioning
confidence: 75%
See 1 more Smart Citation
“…The reduction of friction and temperature takes place by cooling and lubrication action which eventually improves surface roughness. 15 During machining of hard-to-cut with high-speed turning, high-velocity cooling is a favourable technique for better improvement of usage of cutting tool and surface roughness in terms of proper cooling and lubrication. 27 Application of continuous coolant droplets indicates wettability at tool–chip interface and caused easy chip breakage into small segments.…”
Section: Resultsmentioning
confidence: 99%
“…14 A sufficient and more droplet transfer rate of coolants and lubricants with extended adhesion time is required for a high-temperature cutting region in which the applied thin lubricant films reduce the tool wear and improving surface quality of the workpiece. 15–18…”
Section: Introductionmentioning
confidence: 99%